An annually resolved record of Western European vegetation response to Younger Dryas cooling. (1st March 2020) - Obreht, Igor; Wörmer, Lars; Brauer, Achim; Wendt, Jenny; Alfken, Susanne; De Vleeschouwer, David; Elvert, Marcus; Hinrichs, Kai-Uwe
Abstract: The regional patterns and timing of the Younger Dryas cooling in the North Atlantic realm were complex and are mechanistically incompletely understood. To enhance understanding of regional climate patterns, we present molecular biomarker records at subannual to annual resolution by mass spectrometry imaging (MSI) of sediments from the Lake Meerfelder Maar covering the Allerød-Younger Dryas transition. These analyses are supported by conventional extraction-based molecular-isotopic analyses, which both validate the imaging results and constrain the sources of the target compounds. The targeted fatty acid biomarkers serve as a gauge of the response of the local aquatic and terrestrial ecosystem to climate change. Based on the comparison of our data with existing data from Meerfelder Maar, we analyse the short-term environmental evolution in Western Europe during the studied time interval and confirm the previously reported delayed hydrological response to Greenland cooling. However, despite a detected delay of Western European environmental change of ∼135 years, our biomarker data show statistically significant correlation with deuterium excess in Greenland ice core at ∼ annual resolution during this time-transgressive cooling. This suggests a coherent atmospheric forcing across the North Atlantic realm during this transition. We propose that Western European cooling was postponed due to major reorganization of the westerlies that were intermittently forcing warmer and wetter air masses from lower latitudes to Western Europe and thus resulted in delayed cooling relative to Greenland. Highlights: Application of MSI to obtain molecular records at ultra-high temporal resolution. An annually resolved fatty acid data from the Lake Meerfelder Maar covering the Allerød-Younger Dryas transition. Application of molecular-isotopic analyses to constrain the sources of the target fatty acids. Confirmation of previously reported delayed hydrological response to Greenland cooling.